Experimentation and correlates of electronic nicotine delivery system (electronic cigarettes) among university students - A cross sectional study - K.H. Awan (Elsevier, 2016)
Objective: E-cigarettes are becoming popular among youth as safe nicotine delivery systems. Many have expressed concern, however, that e-cigarettes may serve as a gateway to future smoking, given their low perceived risk, or that their use may prevent regular smokers from quitting by maintaining their nicotine addiction. The aim of this study was to assess experimentation with and correlates of e-cigarette use among university students. Material and methods: A cross-sectional study was carried out among 480 university students from four faculties at a university in Riyadh in August-October 2014. A modified version of the World Health Organization's Global Adult Tobacco Survey was used, and multinomial logistic regression was carried out to assess correlations with e-cigarette variables in the whole study sample and among smokers. Results: Almost all students, including the majority of ex-smokers (96.3%) and smokers (94.4%), reported having heard about e-cigarettes. In addition, about one-quarter of the sample (54.2% of smokers, 24.7% of ex-smokers, 6% of never smokers) had experimented with e-cigarettes at least once during their lifetime. Curiosity and peer influence were reported as the main reasons for the use of e-cigarettes. Factors found to be correlated significantly with e-cigarette use were male gender, being a traditional cigarette smoker, having friends who have tried e-cigarettes, and having a strong belief that e-cigarettes could aid smoking cessation. Conclusion: E-cigarettes are popular among Saudi youth, especially among smokers and ex-smokers. Well-designed health education programs and regulatory interventions are required to address this issue. Keywords: E-cigarettes, University students, Smoker, Questionnaire, Prevention